The Epidemiology of Intensive Care Unit Readmissions in the United States - Brown, Sydney E. S. (American Thoracic Society, 2012)
Rationale: The incidence of intensive care unit (ICU) readmissions across the United States is unknown. Objectives: To determine incidence of ICU readmissions in United States hospitals, and describe the distribution of time between ICU discharges and readmissions. Methods: This retrospective cohort study used 196,202 patients in 156 medical and surgical ICUs in 106 community and academic hospitals participating in Project IMPACT from April 1, 2001, to December 31, 2007. We used mixed-effects logistic regression, adjusting for patient and hospital characteristics, to describe how ICU readmission rates differed across patient types, ICU models, and hospital types. Measurements and Main Results: Measurements consisted of 48- and 120-hour ICU readmission rates and time to readmission. A total of 3,905 patients (2%) were readmitted to the ICU within 48 hours, and 7,171 (3.7%) within 120 hours. In adjusted analysis, there was no difference in ICU readmissions across patient types or ICU models. Among medical patients, those in academic hospitals had higher odds of 48- and 120-hour readmission than patients in community hospitals without residents (1.51 [95% confidence interval, 1.12–2.02] and 1.63 [95% confidence interval, 1.24–2.16]). Median time to ICU readmission was 3.07 days (interquartile range, 1.27–6.58). Closed ICUs had the longest times to readmission (3.55 d [interquartile range, 1.42–7.50]). Conclusions: Approximately 2% and 4% of ICU patients discharged to the ward are readmitted within 48 and 120 hours, within a median time of 3 days. Medical patients in academic hospitals are more likely to be readmitted than patients in community hospitals without residents. ICU readmission rates could be useful for policy makers and investigations into their causes and consequences.